2009
DOI: 10.1104/pp.108.134767
|View full text |Cite
|
Sign up to set email alerts
|

The Phloem-Delivered RNA Pool Contains Small Noncoding RNAs and Interferes with Translation    

Abstract: In plants, the vascular tissue contains the enucleated sieve tubes facilitating long-distance transport of nutrients, hormones, and proteins. In addition, several mRNAs and small interfering RNAs/microRNAs were shown to be delivered via sieve tubes whose content is embodied by the phloem sap (PS). A number of these phloem transcripts are transported from source to sink tissues and function at targeted tissues. To gain additional insights into phloem-delivered RNAs and their potential role in signaling, we isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
232
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(246 citation statements)
references
References 50 publications
14
232
0
Order By: Relevance
“…rRNAs and tRNAs, have also been detected in phloem sap exudates. The observation of truncated tRNAs, presenting inhibitory activity in in vitro translation assays is consistent with involvement in a regulatory mechanism to down-regulate protein synthesis [179].…”
Section: Rnas Species and Traffickingsupporting
confidence: 48%
“…rRNAs and tRNAs, have also been detected in phloem sap exudates. The observation of truncated tRNAs, presenting inhibitory activity in in vitro translation assays is consistent with involvement in a regulatory mechanism to down-regulate protein synthesis [179].…”
Section: Rnas Species and Traffickingsupporting
confidence: 48%
“…They appear to be largely involved in signaling 27,28,39 . At the same time, rRNA and tRNAs for almost all amino acids have been observed in the phloem sap of cucurbits 42 . They appear to be selectively transferred into the sieve tube system.…”
Section: Introductionmentioning
confidence: 78%
“…However, we could not find any consensus feature of cleavage sites on the cloverleaf secondary structure of tRNA. Among the studies reporting tRNA fragments, Zhang et al (2009) reported ;58-to 60-ntlong fragments whose cleavage sites fall in the D arm. These fragments could represent the reciprocal fragments generated upon release of tRF-5 series.…”
Section: Discussionmentioning
confidence: 99%
“…tRNA fragments of 30-35 nt have been identified in bacteria, fungi, plants, and animals (Lee and Collins 2005;Haiser et al 2008;Jochl et al 2008;Kawaji et al 2008;Li et al 2008;Thompson et al 2008;Zhang et al 2009). These tRNA fragments are different from the ones reported here in that they are derived from a cleavage at or around the anti-codon loop by Rny1p in yeast (Thompson and Parker 2009) or angiogenin in humans (Yamasaki et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation